Urinary calcium: a promising predictive biomarker for early recognition of environmental lead exposure in children - Nwobi, Nnenna L.; Adedapo, Solomon K.; Oyinlade, Opebiyi A.; Olukolade, Olugbemi; Lagunju, Ikeoluwa A.; Atulomah, Nnodimele O.; Nwazuoke, Ikechukwu A.; Anetor, John I. (International Journal of Research in Medical Sciences, 2019)
Background: In the continuous search for accessible, reliable and sensitive biomarkers for early detection of environmental lead exposure, authors determined the interaction between blood lead level (BLL), the conventional marker of lead exposure, and the indices of calcium and bone metabolism in children. Methods: This cross-sectional study involved 309 apparently healthy children from eight public primary schools in Ibadan, Nigeria who were classified as Elevated BLL (EBLL) and control based on standard cut-off for childhood BLL. BLL, serum Ca (tCa), phosphate, magnesium (Mg), 25-hydroxy-Vitamin D, alkaline phosphatase (ALP), urinary calcium (uCa) and urinary deoxypyridinoline (uDPD) were determined using AAS, HPLC and ELISA as appropriate. Bone-specific ALP (B-ALP) and ionized calcium (iCa) were calculated using standard formulae. Data analyses involved Student’s t-test, Pearson correlation and multivariate regression analysis. p<0.05 was considered statistically significant. Results: BLL and 25-OH-Vitamin D levels were increased in EBLL (0.4±0.1 µmol/L and 60.1±10.7 mmol/L) compared with control (0.2±0.0 µmol/L and 55.1±14.3 mmol/L) p <0.05. No significant differences existed in the levels of ALP, B-ALP, uCa, uDPD, tCa, iCa, phosphate and Mg in both groups (p>0.05). BLL had significant positive correlation with uCa (r=0.176, p=0.002) (p<0.05) but no significant correlation with uDPD, ALP, B-ALP, tCa, iCa, phosphate, Mg and 25-OH-Vitamin D (p>0.05). BLL could be accounted for by uCa by applying the equation, BLL=0.329+0.324uCa. Conclusions: Urinary calcium could be a promising predictive biomarker for early recognition of significant environmental lead exposure in children.